Quantitative Trait Loci Influencing Hb F Levels in Southern Thai Hb E (HBB: c.79G>A) Heterozygotes. (2nd January 2018) - Kesornsit, Aumpika; Jeenduang, Nutjaree; Horpet, Dararat; Plyduang, Thunyaluk; Nuinoon, Manit
Abstract: Variation of fetal hemoglobin (Hb F) expression in heterozygous Hb E ( HBB : c.79G>A) individuals is associated with several genetic modifiers and not well understood. This study was undertaken in order to determine the effect of single nucleotide polymorphisms (SNPs), including Xmn I G γ (rs7482144), rs766432 on the BCL11A gene and rs9376074 on the HBS1L gene, on Hb F levels in Southern Thai heterozygous Hb E individuals. A total of 97 Southern Thai subjects carrying heterozygous Hb E were selected for the hematological study. After excluding the samples with α-thalassemia (α-thal) interaction or moderate anemia, because both conditions can affect the hematological parameters, the remaining 74 samples were submitted to SNP analysis. Hematological parameters were measured using an automated hematology analyzer and high performance liquid chromatography (HPLC). The results show that rs766432 was strongly associated with increased Hb F levels and rs7482144 was associated with Hb F levels in each subgroup (genotype) of rs766432. This study suggested that the BCL11A locus has a major effect on Hb F levels compared with the Xmn I polymorphism in Hb E heterozygotes. This association of Hb F levels with SNPs is useful for the interpretation of hemoglobin (Hb) typing in heterozygous Hb E samples with high Hb F levels. Future research will need to address the better understanding of the mechanisms of the SNPs that regulate Hb F production without stress erythropoiesis in Hb E heterozygotes.